Enhanced polyethylene terephthalate (PET) glycolysis with biochar-supported organic ionic liquid-based catalysts - Stuart Conroy; Fraser Norris; Elliot Ross; Stuart D. Robertson; Yong Xu; Ashleigh J. Fletcher; Xiaolei Zhang (Journal of Environmental Chemical Engineering, 2026)

Performance of water-based fixed fire fighting systems in road tunnels: A review - Tao Deng; Stuart Norris; Mingnian Wang; Li Yu; Zhiguo Yan; Rajnish N. Sharma (Tunnelling and Underground Space Technology, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Plastic ingestion and trace element contamination of Manx shearwaters Puffinus puffinus on the Faroe Islands - William F. Mills; Catrin Norris; Stuart Black; Richard A. Phillips; Sjúrður Hammer; Bergur Olsen; Jóhannis Danielsen (Marine Pollution Bulletin, 2024)

Stability of smoke stratification under the impact of water sprays with various droplet size ranges in longitudinally ventilated road tunnels - Tao Deng; Stuart Norris; Rajnish N. Sharma (Tunnelling and Underground Space Technology, 2023)

Stratification and temporal evolution of mixing regimes in diurnally heated river flows - Cindy Nguyen-Dang; Nicholas Williamson; Steven W. Armfield; Michael P. Kirkpatrick; Stuart E. Norris (Environmental Fluid Mechanics, 2023)
Direct numerical simulations of stratified open channel flows subject to a varying surface heat flux are performed. The influence of the diurnal heating time on the spatial and temporal variation of mixing in the flow and the characteristics of the mean flow state are examined. The control parameters are the bulk stability parameter $$λ_{B}$$ λ B , defined through the ratio of the channel height $$δ$$ δ and a bulk Obukhov length scale $$\mathscr{L}_{B}$$ L B , and the diurnal time scale $$\hat{t}$$ t ^ , defined as the ratio of the heating time to an eddy turnover time. The Prandtl number Pr and Reynolds number $$Re_{τ}$$ R e τ have values of 1 and 400. Simulations are performed over $$\hat{t} = 1$$ t ^ = 1 to 24 and $$λ_{B} = 0.6$$ λ B = 0.6 to 26. Two key flow features are used to classify the flow regimes observed, namely the laminar layer depth (LLD) and stratified layer depth (SLD) where the LLD is defined as the depth from the free surface when the buoyancy Reynolds number $$Re_{B} ≈ 7$$ R e B ≈ 7 and the SLD is the depth from the free surface when the turbulent Froude number $$Fr ≈ 1$$ F r ≈ 1 . This study attempts to characterise how these length scales vary across the diel cycle. The LLD is a viscous length scale and a regime map of a viscous parameter, the bulk Obhukov Reynolds number $$Re_\mathscr{L}$$ R e L , and $$\hat{t}$$ t ^ is presented to classify the LLD behaviour. A regime map of $$λ _{B}$$ λ B and $$\hat{t}$$ t ^ is presented to classify the behaviour of the SLD. Three classifications for each layer depth behaviour within a diel cycle form the basis of the regime maps for this paper: a neutral flow where the LLD or SLD does not exist (denoted by NL and NS), a stratified flow where the LLD or SLD are diurnally varying (denoted as DL and DS) and a persistent layer of the LLD or SLD (denoted as PL and PS). The transition between the NL to DL is $$\hat{t} \propto Re_{\mathscr{L}}^{4.5}$$ t ^ ∝ R e L 4.5 , DL to PL is $$\hat{t} \propto Re_{\mathscr{L}}^{- 0.5}$$ t ^ ∝ R e L - 0.5 , NS to DS is $$\hat{t} \propto λ _{B}^{0}$$ t ^ ∝ λ B 0 and DS to PS is $$\hat{t} \propto λ _{B}^{1}$$ t ^ ∝ λ B 1 . The regime maps may be used as a predictive tool to determine when suppressed mixing regimes occur in rivers. At each flow depth, the flow sweeps though a range of mixing states across the diel cycle. The local mixing efficiency are briefly assessed and found to scale well with the instantaneous $$Fr$$ Fr number according to the regimes proposed by Garanaik and Venayagamoorthy ( J. Fluid Mech. , vol. 867, 2019, pp. 323-333).

A review of computational fluid dynamics application to investigate tropical cyclone wind speeds - Muizz Shah; Stuart E. Norris; Richard Turner; Richard G. J. Flay (Natural Hazards, 2023)

Numerical study of the flame geometry of pool fires in longitudinally ventilated tunnels - Tao Deng; Stuart Norris; Rajnish N. Sharma (Tunnelling and Underground Space Technology, 2023)

Warming world, changing ocean: mitigation and adaptation to support resilient marine systems - Rowan Trebilco; Aysha Fleming; Alistair J. Hobday; Jess Melbourne-Thomas; Amelie Meyer; Jan McDonald; Phillipa C. McCormack; Kelli Anderson; Narissa Bax; Stuart P. Corney; Leo X. C. Dutra; Hannah E. Fogarty; et al. (Reviews in Fish Biology and Fisheries, 2022)

Connecting to the oceans: supporting ocean literacy and public engagement - Rachel Kelly; Karen Evans; Karen Alexander; Silvana Bettiol; Stuart Corney; Coco Cullen-Knox; Christopher Cvitanovic; Kristy de Salas; Gholam Reza Emad; Liam Fullbrook; Carolina Garcia; Sierra Ison; et al. (Reviews in Fish Biology and Fisheries, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

A boreal songbird's 20,000 km migration across North America and the Atlantic Ocean - William V. DeLuca; Bradley K. Woodworth; Stuart A. Mackenzie; Amy E. M. Newman; Hilary A. Cooke; Laura M. Phillips; Nikole E. Freeman; Alex O. Sutton; Lila Tauzer; Carol McIntyre; Iain J. Stenhouse; Scott Weidensaul; et al. (Ecology, 2019)

Hemodynamics in Idealized Stented Coronary Arteries: Important Stent Design Considerations - Susann Beier; John Ormiston; Mark Webster; John Cater; Stuart Norris; Pau Medrano-Gracia; Alistair Young; Brett Cowan (Annals of Biomedical Engineering, 2016)